2019
DOI: 10.1111/mec.15210
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the viral content of uncultured picoeukaryotes in the global‐ocean by single cell genomics

Abstract: Viruses are the most abundant biological entities on Earth and have fundamental ecological roles in controlling microbial communities. Yet, although their diversity is being increasingly explored, little is known about the extent of viral interactions with their protist hosts as most studies are limited to a few cultivated species. Here, we exploit the potential of single‐cell genomics to unveil viral associations in 65 individual cells of 11 essentially uncultured stramenopiles lineages sampled during the Tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 108 publications
(185 reference statements)
0
13
0
Order By: Relevance
“…In the resulting phylogenetic trees, EMALE core proteins formed monophyletic clades with mavirus and related sequences from environmental samples, thus significantly expanding the known diversity of the genus Mavirus . The environmental sequences that clustered with EMALE core proteins include a single amplified genome (SAG) from an uncultured chrysophyte ( Castillo et al, 2019 ), the metagenomic Ace Lake Mavirus (ALM) ( Zhou et al, 2013 ), and four additional metagenomes that were identified in a global survey of virophage sequences ( Paez-Espino et al, 2019 ). The chrysophyte SAG is nearly identical to mavirus strain Spezl and indicates that the host range of mavirus extends beyond bicosoecids.…”
Section: Resultsmentioning
confidence: 99%
“…In the resulting phylogenetic trees, EMALE core proteins formed monophyletic clades with mavirus and related sequences from environmental samples, thus significantly expanding the known diversity of the genus Mavirus . The environmental sequences that clustered with EMALE core proteins include a single amplified genome (SAG) from an uncultured chrysophyte ( Castillo et al, 2019 ), the metagenomic Ace Lake Mavirus (ALM) ( Zhou et al, 2013 ), and four additional metagenomes that were identified in a global survey of virophage sequences ( Paez-Espino et al, 2019 ). The chrysophyte SAG is nearly identical to mavirus strain Spezl and indicates that the host range of mavirus extends beyond bicosoecids.…”
Section: Resultsmentioning
confidence: 99%
“…The sharing of nearly identical viral sequences across multiple eukaryote phyla within the GoM protists (Figure 3) also makes it unlikely that these viruses are integrated into protistan genomes. Earlier single cell genomics studies of protists in marine environments have reported the presence of bacteriophage, ssDNA and other virus sequences in individuals such as Picozoa (Yoon et al, 2011), Cercozoa (Bhattacharya et al, 2012), and Stramenopiles (Roy et al, 2014;Castillo et al, 2019). In these cases, identified viruses were hypothesized to be either infecting the protist (Yoon et al, 2011), bacterial viruses originating from infected bacterial prey or epibionts (Yoon et al, 2011;Bhattacharya et al, 2012), or simply removed from analysis without further consideration (Roy et al, 2014).…”
Section: Nature Of Associations Of Protists and Virusesmentioning
confidence: 99%
“…In the resulting phylogenetic trees, EMALE proteins formed monophyletic clades with mavirus and related sequences from environmental samples, thus significantly expanding the known diversity of the genus Mavirus. The environmental sequences that clustered with EMALE proteins include a single amplified genome (SAG) from an uncultured chrysophyte 29 , the metagenomic Ace Lake Mavirus (ALM) 30 , and four additional metagenomes that were identified in a global survey of virophage sequences 23 . The chrysophyte SAG is nearly identical to mavirus strain Spezl and shows that the host range of mavirus is broader than previously assumed.…”
Section: Phylogenetic Analysis Of Emale Core Genesmentioning
confidence: 99%